The diagnosis and management of inhalation injury: An evidence based approach. Issue 5 (August 2018) - Deutsch, C.J.; Tan, A.; Smailes, S.; Dziewulski, P.
Highlights: Fibreoptic bronchoscopy is a relatively strongly supported diagnostic modality. Nebulized heparin can be supported by a reasonable clinical evidence base. High frequency oscillatory ventilation and exogenous surfactant may be promising. Empirical antimicrobials and steroids are not recommended. Evidence-based smoke inhalation management is marred by a lack of human studies. Abstract: Introduction: Smoke inhalation injury (II) is an independent risk factor for mortality in burns and its management is inherently complex. We aim to make recommendations for best practice in managing II and its sequelae by reviewing all available current evidence in order to provide an evidence-based approach. Methods: We conducted a systematic search of the Cochrane database and Embase using PRISMA guidelines with no patient population exclusion criteria. Published work was reviewed and evidence levels graded. Results: We identified 521 abstracts for inclusion. Of the 84 articles identified for secondary review, 28 papers were excluded leaving 56 papers suitable for final inclusion. Conclusions: We are able to identify a number of strategies in both diagnosis and treatment of II that have support in the published literature, including the role of bronchoscopy, permissive hypercapnia, nebulized heparin and hydroxycobalamin. Other strategies have not been shown to be harmful, but their efficacy is also not firmly established, such as high frequency oscillatory ventilation and exogenous surfactant. Prophylactic antibiotics and corticosteroids are not recommended. In general, published evidence for II is mostly Level 3 or below, due to a noticeable lack of large-scale human studies. This represents a challenge for evidence-based burns practice as a whole.